Managing halal foods through power collaboration between supply chain actors - Akbarizan, Akbarizan (International Business Information Management Association, IBIMA, 2016)
Labeling Halal foods must consider the difficulty to achieve the business goal by individual organizations because relationships between supply chain actors in Halal foods is affected by the power collaboration an entity to influence another entity to ensure quality assurance system. The purpose of this paper develops a conceptual framework of supply chain Halal foods with considering the power collaboration between supply chain actors from a literature review. The framework is conducted using the SCOR model as modeling tool to investigate the power collaborations between suppliers, manufacturers, distributors and buyers in producing Halal foods. Finding of this study provides a conceptual framework of supply chain Halal foods to develop effective collaborations within the partnerships. Further research suggests conducting other factors that can affect the supply chain Halal foods involving regulations for each region that implement the policy of Halal foods in greater detail.